CONSIDERATIONS REGARDING THE DEVELOPMENT OF A SPECIFIC SPECIMEN FOR THE ANALYSIS OF COSTS IN AGRICULTURE - Dan BODESCU; Gavril ȘTEFAN; Dan CAZACU; Alexandru Sorin TUDORAN; Adriana MĂGUREANU; Oana COCA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the research presented in this paper is to develop a specific sample model for the analysis of costs in agriculture which was done by: 1. Scientific documentation to determine the main criteria to determine the relevance of including farm size ranges in the sampling structure; 2. sensitivity analysis in order to measure the impact of each criterion on farm-specific economic performance; 3. Interviews with farmers from a representative sample for the evaluation of farms by size categories; 4. restructuring the size ranges. The field researches were carried out in the second half of 2020, on two development regions of Romania: NE and SE. The average general score obtained by the entire sample is 4.7, which resulted in a structure of agricultural farms in economic size consisting of V intervals with the following limits: 100,000 SO, 250,000 SO, 500,000 SO, 750,000 SO, 1,000,000 SO.